(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The International Energy Agency’s Ocean Energy Systems (IEA-OES) Technology Collaboration Programme provides a global framework to accelerate the sustainable development of ocean energy technologies. Through its programme, IEA-OES addresses all water-powered energy sources, including waves, tidal streams, ocean currents, ocean thermal energy conversion (OTEC), and salinity gradients, fostering innovation and collaboration among 21 member countries and the European Commission. Its roadmap "Ocean Energy and Net Zero: An International Roadmap to Develop 300 GW of Ocean Energy by 2050", outlines a vision for achieving 300 GW of capacity, 680,000 jobs, 340 billion in gross value added, and significant carbon emission reductions by 2050. The roadmap emphasizes the need for international cooperation, robust policy mechanisms, and technological advancement to scale the sector effectively. Complementing this, the Stage Gate Metrics Framework offer a systematic approach to assess and track technology readiness across milestones, ensuring transparency and risk mitigation. Other key initiatives include the OES-Environmental Task, streamlining consenting processes and evaluating environmental impacts, the Economics of OTEC study addressing cost barriers, and collaborative numerical modeling of wave energy technologies and tidal resource. Through these initiatives, the IEA-OES work programme provides essential guidance for technology development and policy formulation, enabling the effective integration of ocean energy into global energy systems and supporting the transition to a sustainable, low-carbon future.